The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/978-3-319-04981-6_50
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intraarterial Administration of Fasudil Hydrochloride for Preventing Symptomatic Vasospasm After Subarachnoid Hemorrhage

Abstract: IAFC significantly reduced the cerebral circulation time after aneurysmal SAH and might be effective for the prevention of symptomatic vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Fasudil has been primarily studied in Japan and is currently utilized in Japan for vasospasm prophylaxis . Because of the limited number of trials, it is not as popular elsewhere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasudil has been primarily studied in Japan and is currently utilized in Japan for vasospasm prophylaxis . Because of the limited number of trials, it is not as popular elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Fasudil has been primarily studied in Japan and is currently utilized in Japan for vasospasm prophylaxis. 89 Because of the limited number of trials, it is not as popular elsewhere. Large randomized, controlled clinical trials are needed to further establish the benefit of fasudil in aSAH.…”
Section: Fasudilmentioning
confidence: 99%
“…Fasudil [1-(5-isoquinolinesulfonyl)-homopiperazine] is a well-described orally available Rho kinase inhibitor, 26 which has been approved in Japan and China for the treatment of cerebral vasospasm following surgery for associated cerebral ischemic symptoms. 29 Following p.o. administration, Fasudil is converted into the active metabolite 1-(hydroxy-5-isoquinoline sulfonyl-homopipera-zine) (Fasudil-OH).…”
Section: Discussionmentioning
confidence: 99%
“…Rock contributes to vasoconstriction via activation of multiple molecular targets including Ca 2+ sensitization of the VSMC contractile apparatus, actin polymerization and actin filament stabilization (20). Clinical trials have shown that Rock inhibition is an additional therapeutic option to resolve vasospasms (21,22 (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 may activate the RhoA-rho-kinase (Rock) pathway in mesenteric arterial vascular smooth muscle cells (VSMCs) which sensitizes the contractile apparatus to Ca 2+ causing a hyper-contractile state that leads to vasospasms (20). Rock inhibitors have been shown to resolve coronary and cerebral arterial spasms in patients (21,22) while data on the potential of Rock inhibitors to antagonize vasoconstrictions in human mesenteric arteries are sparse. Therefore, the aims of this study were 1) to characterize the responses of human mesenteric arteries to physiological vasoconstrictors that may contribute to the development of NOMI;…”
Section: Introductionmentioning
confidence: 99%